PENGARUH EKSTRAK PROTEIN KACANG KOMAK (Lablab purpureus (L.) Sweet) PADA KADAR GLUKOSA DAN PROFIL LIPIDA SERUM TIKUS DIABETES [Effect of Protein Extract of Hyacinth Bean (Lablab purpureus (L.) sweet) on Glucose and Lipid Profiles Serum In Diabetic Rats] - Arif - Hartoyo; Deddy - Muchtadi; Made - Astawan; Dahrulsyah - -; Adi - Winarto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2011)
The objectives of this research were to evaluate the effect of Lablab protein extract in diet on blood glucose concentration and lipid profiles of alloxan-induced diabetic rats. Two month old male Sprague Dawley rats were divided into 4 groups, containing 5 rats in each group. Three groups were diabetic rats induced by alloxan injection (110 mg/kg of body weight by intra-pheritonial injection) while one group was a normal rat as a control. The experimental groups were normal group, diabetic group, diabetic+cholesterol 0.5% group, and diabetic+cholesterol 0.5% + Lablab protein group. The concentration of rat’s blood glucose were periodically measured during diet intervenion (day 0,14,27, and 42). The result demonstrated that after 42 day of intervention, diet containing Lablab protein extract decreased the blood glucose concentration sharply from 455,75 mg/dl to 104.50 mg/dl (77%), while glucose concentration of control group only descreased from 458 mg/dl to 455.33 mg/dl (0.6%). Lablab protein diet significantly (p<0.05) reduce the concentration of blood glucose as compared to the control group. Lablab protein diet had a significant effect (p<0.05) on the reduction of serum total cholesterol, LDL cholesterol and triglycerides. Lablab protein diet seem to be benefecial for treating hyperglikemia and preventing diabetic complications.